THE EFFECT OF INQUIRY TRAINING LEARNING MODEL USING MACROMEDIA FLASH AND CREATIVE THINKING ABILITY ON SCIENCE PROCESS SKILLS OF STUDENT - Helena Evadonna Siagian; Nurdin Bukit; Derlina . (Universitas Negeri Medan, 2016)
The aims of this research were to analyze science process skills of students using Inquiry Training Learning Model use Macromedia Flash on science process skills of students compare using conventional learning, analyze science process skills ofstudents who have high category in creative thinking ability better than low category in creative thinking ability, and analyze the interaction between Inquiry Training learning model use Macromedia Flash and the level of creative thinking ability in improving the science process skills. The research type was quasi experiment andtwo group pretest-posttest designs were used in this study. The sample was choosen by using cluster random class technique. The instrument was consist of science process skills test and creative thinking ability test. Data in this research was analyzed by using twoway Anova. The results of this research showed that the inquiry training learning model use macromedia flash was better than conventional learning in improving the students science process skills, the science process skills of the students who had highcategory in creative thinking ability was better than low category, and there was interaction between inquiry training learning model use macromedia flash and the level of creative thinking ability in improving students science process skills.